Improving Leadership Competence Among Undergraduate Nursing Students: Innovative Objectives Development, Implementation, and Evaluation. Issue 1 (6th January 2022) - Hsieh, Li-Wei; Chang, Yu-Chun; Yen, Miaofen
Abstract : Supplemental digital content is available in the text. Abstract: AIM: The aim of the study was to identify baccalaureate nursing leadership objectives and evaluate their effectiveness when embedded into an undergraduate nursing curriculum. BACKGROUND: The objectives of nursing leadership competencies cannot be met in one semester but must be gradually developed over successive courses. METHOD: A list of learning objectives for leadership competence was generated and reviewed by 12 experts using the Delphi method. The consensuses objectives were embedded into a four-year nursing baccalaureate curriculum in Taiwan. Nursing students ( N = 120) who participated in the courses evaluated the embedded objectives of leadership competency introduced in their undergraduate nursing program. Leadership competence was improved among students on nine items ( t = 2.282 to 5.741, p = .001 to .030) of the Nursing Leadership Competence Assessment Scale for Undergraduate Nursing Students. CONCLUSION: The results can serve as a reference for universities seeking to promote nursing leadership education.